2011
DOI: 10.1073/pnas.1103546108
|View full text |Cite
|
Sign up to set email alerts
|

Cellular correlate of assembly formation in oscillating hippocampal networks in vitro

Abstract: Neurons form transiently stable assemblies that may underlie cognitive functions, including memory formation. In most brain regions, coherent activity is organized by network oscillations that involve sparse firing within a well-defined minority of cells. Despite extensive work on the underlying cellular mechanisms, a fundamental question remains unsolved: how are participating neurons distinguished from the majority of nonparticipators? We used physiological and modeling techniques to analyze neuronal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
183
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(197 citation statements)
references
References 51 publications
13
183
1
Order By: Relevance
“…We tested whether increasing the occurrence of SPW-Rs, and associated antidromic action potential firing (11), would result in changes in synaptic strength in the hippocampal CA1 region. It has been demonstrated that GABA A receptor activation, which depolarizes axons and hyperpolarizes somatodentritic regions, facilitates antidromic spike generation in CA1 neurons during SPW-Rs (11,12). Our studies show that local injection of muscimol, a GABA A receptor agonist, to axons in the alveus evoked depression of synaptic responses, which lasted for 90 min after muscimol withdrawal (Fig.…”
Section: Facilitation Of Spontaneous Spw-rs Leads To Reduction In Synmentioning
confidence: 68%
See 3 more Smart Citations
“…We tested whether increasing the occurrence of SPW-Rs, and associated antidromic action potential firing (11), would result in changes in synaptic strength in the hippocampal CA1 region. It has been demonstrated that GABA A receptor activation, which depolarizes axons and hyperpolarizes somatodentritic regions, facilitates antidromic spike generation in CA1 neurons during SPW-Rs (11,12). Our studies show that local injection of muscimol, a GABA A receptor agonist, to axons in the alveus evoked depression of synaptic responses, which lasted for 90 min after muscimol withdrawal (Fig.…”
Section: Facilitation Of Spontaneous Spw-rs Leads To Reduction In Synmentioning
confidence: 68%
“…Disrupting SPW-Rs, and therefore replay, impairs memory retention (9, 10), suggesting that replay of activity sequences during resting states is critical for memory consolidation. However, little is known of how synaptic strength may be affected by SPW-Rs' that are associated with memory consolidation in the hippocampus.Recent studies demonstrate that a distinguishing feature of individual CA1 hippocampal neurons that participate in SPW-Rs is firing of antidromic action potentials generated spontaneously in the distal region of axons in a nonclassical mode (ectopically) (11,12). Ectopic spike generation is facilitated by GABAmediated axonal depolarization and electrotonic coupling through axonal gap junctions (11, 13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During fast network oscillations, almost all local neurons are phasically inhibited on every oscillation cycle, and most of this inhibition is perisomatic, i.e., at the soma, the proximal dendrites and the axon initial segment. 35,52,87,107 In neuronal networks of the hippocampus proper, fast-spiking PV þ interneurons form numerous GABAergic synaptic contacts to pyramidal cells in the perisomatic region 23,87 ( Figures 1C-E). As outlined above, these synapses are strongly and rhythmically activated during fast network oscillations, and multiple lines of evidence indicate that this phasic inhibition is a key factor in coordinating neuronal activity during network states such as gamma oscillations or sharp wave-ripple complexes.…”
Section: Energy Utilization Of Fast-spiking Behavior and Synaptic Inhmentioning
confidence: 99%